White/Right Shakespeare: Whiteness in the Field of Early Modern Studies - Mendoza, Kirsten N. (Early Theatre, 2025)
This review essay considers whiteness in Shakespeare and early modern studies through five books: David Sterling Brown’s Shakespeare’s White Others; Miles Grier’s Inkface: Othello and White Authority in the Era of Atlantic Slavery; Farah Karim-Cooper’s The Great White Bard: How to Love Shakespeare While Talking About Race; White People in Shakespeare: Essays on Race, Culture and the Elite, edited by Arthur L. Little, Jr; and Ian Smith’s Black Shakespeare: Reading and Misreading Race.